INCLUSIVE EDUCATION IN ELEMANTARY SCHOOL: AN EVALUATIVE STUDIES ON EDUCATIONAL INCLUSION IN WEST JAKARTA - Mohamad Syarif Sumantri; Rosa Sagala; Syamsul Syamsul (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2017)
This study aimed to evaluate the implementation of the policy of inclusive education programs. Research using qualitative, evaluative and descriptive models based on Stake. The results showed that the input (antecedents) states that the implementation of inclusive education programs at both schools is not optimal in accordance with the guidelines for the implementation of inclusive education. Process (transcations) First, the lesson plan, due to the lack of identification and assessment at the time of admission of learners new learners, then it affects the planning of lessons to children with special needs. Second, the learning process, children with special needs that exist in every class together to learn with children in general. Third, assessment or evaluation of learning, not demanding graduation competency to children with special needs. The results (outcomes) First, the academic assessment for children with special needs are not prosecuted together with children in general. Second, the social skills of children with special needs children in general, peers. Based on the results of this research can be concluded that the implementation of policies on inclusive education program still needs improvement efforts both on the evaluation of the input (antecedents), process (transcations) and results (outcomes).